Elotuzumab monotherapy in patients with smouldering multiple myeloma: a phase 2 study. (29th May 2018) - Jagannath, Sundar; Laubach, Jacob; Wong, Ellice; Stockerl‐Goldstein, Keith; Rosenbaum, Cara; Dhodapkar, Madhav; Jou, Ying‐Ming; Lynch, Mark; Robbins, Michael; Shelat, Suresh; Anderson, Kenneth C.; Richardson, Paul G.
Summary: Smouldering multiple myeloma (SMM) is associated with increased risk of progression to multiple myeloma within 2 years, with no approved treatments. Elotuzumab has been shown to promote natural killer (NK) cell stimulation and antibody‐dependent cellular cytotoxicity (ADCC) in vitro . CD56 dim (CD56 dim /CD16 + /CD3 − /CD45 + ) NK cells represent the primary subset responsible for elotuzumab‐induced ADCC. In this phase II, non‐randomized study (NCT01441973), patients with SMM received elotuzumab 20 mg/kg intravenously (cycle 1: days 1, 8; monthly thereafter) or 10 mg/kg (cycles 1, 2: weekly; every 2 weeks thereafter). The primary endpoint was the relationship between baseline proportion of bone marrow‐derived CD56 dim NK cells and maximal M protein reduction; secondary endpoints included overall response rate (ORR) and progression‐free survival (PFS). Fifteen patients received 20 mg/kg and 16 received 10 mg/kg; combined data arepresented. At database lock (DBL, September 2014), no association was found between baseline CD56 dim NK cell proportion and maximal M protein reduction. With minimum 28 months' follow‐up (DBL: January 2016), ORR (90% CI) was 10% (2·7–23·2) and 2‐year PFS rate was 69% (52–81%). Upper respiratory tract infections occurred in 18/31 (58%) patients. Four (13%) patients experienced infusion reactions, all grade 1–2. Elotuzumab plus lenalidomide/dexamethasone is under investigation for SMM.